ダイ19ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1978-1979 - 平沢, 威男; ヒラサワ, タケオ; Hirasawa, Takeo (1982)
P(論文) 第19次越冬隊30名は, 1978年2月から1979年1月までの1年間, 昭和基地とみずほ基地を中心として, 国際磁気圏観測計画(IMS)に対応したオーロラ現象の総合観測を実施した。また, これらのIMS観測に加えみずほ基地では雪氷, 気象, 昭和基地周辺の沿岸地域では生物, 医学などの観測が行われた。 As a major enterprise of the International Magnetospheric Study (IMS) which was conducted in 1976-1978,the coordinated observations were carried out in Antarctica in order to acquire a full understanding of upper atmosphere disturbances in the polar regions. The 19th wintering party of the Japanese Antarctic Research Expedition (1978-1979) consisting of thirty members was mainly in charge of research activities for the Antarctic IMS projects. Six sounding rockets (four S-310JA and two S-210JA) were launched into auroras from Syowa Station in 1978. Through the successful rocket flights, significant physical quantities within auroras were measured : namely, profiles of the electron density and temperature in the ionosphere, energy spectra of precipitating electrons, frequency spectra of VLF and HF plasma waves, vertical profiles of electric and magnetic fields, profiles of auroral X-rays, and vertical profiles of NO and O_3 concentration. A geomagnetic meridional station array which contained two manned stations and one unmanned observatory was constructed for observing the space-time variations of auroral phenomena. By satellite data acquisition facilities, the data from ISIS-1 and 2 satellites and Japanese polar-orbiting satellite Kyokko were received on a routine basis. In addition to the above IMS observations, the inland observation for the glaciological and meteorological studies and the coastal traverse for the biological study were also carried out around Syowa Station for the period from February 1978 to January 1979. departmental bulletin paper